Ethics for Social Impact Ethical Decision-Making in Nonprofit Organizations - Handy, Femida (Springer International Publishing, 2018)
This book outlines the various elements involved in ethical decision-making for nonprofit leaders, and whose rights to prioritize when facing complex situations. Nonprofit board members and employees are often placed in difficult situations, with no single stakeholder and an allegiance to mission statements whose outcomes can be difficult to measure. While nonprofit charitable organizations are generally considered more trustworthy than their counterparts in the public or for-profit sector, when scandals and wrongdoings are uncovered, they must be dealt with in ethical ways. Through a case study approach, this book delivers clear ethical decision-making frameworks and promotes robust reflection on how to arrive at different decision points and throw light on elements that are often ignored or assumed. Ultimately, it offers students, researchers, and managers a practical approach to the ambiguous question, what is the ethical way.